THE ROLE OF TEACHERS’ PROFESSIONAL COMPETENCE IN IMPROVING THE QUALITY OF TAHFIDZ AL-QUR’AN LEARNING AT MIN 2 JEPARA - Siti Mariyam; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to describe and analyse the role of teachers’ professional competence in improving the quality of Tahfidz Al-Qur’an (Qur’an memorization) learning at Madrasah Ibtidaiyah Negeri (MIN) 2 Jepara, Central Java, during the 2025/2026 academic year, including its supporting and inhibiting factors and the resulting improvements. Although tahfidz programs have expanded rapidly within Indonesia’s formal madrasahs, many tahfidz teachers possess strong memorization but limited pedagogical and professional competence, which weakens the consistency, accuracy, and durability of students’ memorization. The research uses a qualitative descriptive (case-study) design. Data were collected through non-participant observation, structured interviews with the madrasah principal, the deputy head of curriculum, and tahfidz teachers, and documentation. Source triangulation was used to establish data validity, and the data were analysed using the Miles and Huberman interactive model (data collection, data reduction, data display, and conclusion drawing/verification). The findings indicate that teachers’ professional competence operates through four interrelated functions: mastery of Qur’anic material (mutqin memorization, tajwid, makharij al-huruf), command of tahfidz methods (talaqqi, tikrar, tasmi’, and scheduled muroja’ah), design of developmentally appropriate learning strategies, and continuous, criterion-based evaluation of memorization. Supporting factors include a structured curriculum, a Qur’anic school climate, and parental involvement, whereas inhibiting factors include heterogeneous student ability, time and facility constraints, and uneven home support. Strengthening professional competence is associated with improved fluency, tajwid accuracy, memorization strength, and Qur’anic character. The study contributes a competence-based model for assuring tahfidz learning quality in primary madrasahs.